Algeria : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
In this study, the following are represented in the form of tabulation: basic economic and financial indicators, supply and usage of resources, sectoral distribution of GDP, production, exports, and consumption of liquid petroleum products, domestic prices of major energy products, agricultural and land use patterns, crop yields, indices of industrial production, production of minerals, housing supply, consumer index, household supply, central government revenue, expenditure, and monetary survey, hydrocarbon exports, and trade indices. They are listed based on statistical information.